Not one segment: using global and local BoP characteristics to model country-specific consumer profiles. Issue 3 (13th May 2019) - Lappeman, James; Ransome, Kristin; Louw, Zach
Abstract : Purpose: This paper aims to show that a generic bottom-of-the-pyramid (BoP) segmentation strategy does not represent a multi-country BoP consumer profile. A series of multinational entry failures has clearly shown that a one-size-fits-all strategy is inappropriate for emerging markets, especially in Africa. Design/methodology/approach: The study analysed literature defining and profiling BoP consumers at both a global and local level using South Africa as a case study. Being Africa's largest economy, South Africa was an ideal subject. The findings were then independently triangulated with seven experts for validation. Findings: The results show that the South African BoP has eight characteristics that align with definitions in global BoP consumer literature. An additional five characteristics were identified that were not general BoP characteristics, and that applied specifically to South Africa. Practical implications: The findings add to the growing evidence that BoP markets are complex and heterogeneous, and they make a case to consider each BoP market individually. As there is yet to be a model to define BoP market differences systematically, this study provides a foundation for new developments in BoP segmentation in Africa and in other emerging markets. Originality/value: While there is evidence that BoP markets are complex and heterogeneous, there is yet to be a model to begin the process of defining these differences systematically to improve strategic direction for multinational companies and regional decision makers. This study, therefore, provides a foundation for new developments in this field of segmentation in Africa and in other emerging markets globally.